Как волк службу искал: [сказки / художники И. и В. Пустоваловы] - Пустовалова Ирина (Читаем сами, 2015)
Экземпляры: ф.5 (20171004) / Инвентарный номер: 49301 / Цена: 64.00 / Сис.шифр: Д / Авт.знак: К 16 / ГРНТИ: 17.71 / ББК: 82.3(2)